DAMPAK ASEAN ECONOMIC COMMUNITY (AEC) TERHADAP TENAGA KERJA INDONESIA DI SINGAPURA - Bella Amallia; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explains the effect of current labor as a form of a blueprint strategy schedule for a scheme against the ASEAN Economic Community (AEC) on Indonesian labor to Singapore. ASEAN Economic Community (AEC) 2015 will open more opportunities to liberate the flow of goods, services, investment, working capital through the ASEAN region. On the one hand, the impact of the free flow of the ASEAN Economic Community (AEC) will provide an opportunity to facilitate the performance of Indonesia's labor competitiveness. Efforts to increase competitiveness to the ASEAN market will provide optimal results if accompanied by promoting cooperation among foreign workers in ASEAN through a regional production network. On the other hand, the ASEAN Economic Community (AEC) labor flows will also pose a threat to Indonesia and the domestic market if entrepreneurs and governments have not yet prepared for this new era of competition in ASEAN. As ASEAN member countries generate more skilled foreign workers, the challenge for Indonesia is to generate competitive and productive labor based on differentiation, efficiency and innovation.This research uses a liberal perspective that supports the international economy based on free trade, because it involves cooperation in trade between Indonesia and Singapore. The data sources used in this study are books, journals, working papers, and valid news from the website.The implementation of the ASEAN Economic Community Blueprint will have implications for the Indonesian and ASEAN economies in terms of competitive conditions between labor resources and the composition of international trade.Key words : ASEAN Economic Community 2015,Labor, Liberalism Perspective